2020
DOI: 10.3390/f11101100
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Variability Indicated by False Rings in Bald Cypress (Taxodium distichum (L.) Rich.)

Abstract: Despite growing in wet lowland and riparian settings, Taxodium distichum (L.) Rich. (bald cypress) has a strong response to hydroclimate variability, and tree ring chronologies derived from bald cypress have been used extensively to reconstruct drought, precipitation and streamflow. Previous studies have also demonstrated that false rings in bald cypress appear to be the result of variations in water availability during the growing season. In this study 28 trees from two sites located adjacent to the Choctawha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…(bald cypress; Table 3). As the longest-lived tree species in eastern North America, T. distichum has been shown to provide a valuable annual archive of multi-millennial paleo-hydroclimate conditions [3,8,9,14,29,31], and thus is ideal for developing these long reconstructions. Three TRCs were retained in the Choctawhatchee (Newton), Conecuh and Escambia River models, and two were retained by the Choctawhatchee (Bruce) and Perdido River models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(bald cypress; Table 3). As the longest-lived tree species in eastern North America, T. distichum has been shown to provide a valuable annual archive of multi-millennial paleo-hydroclimate conditions [3,8,9,14,29,31], and thus is ideal for developing these long reconstructions. Three TRCs were retained in the Choctawhatchee (Newton), Conecuh and Escambia River models, and two were retained by the Choctawhatchee (Bruce) and Perdido River models.…”
Section: Resultsmentioning
confidence: 99%
“…While dendrochronological reconstructions of hydroclimate, including streamflow, have been widely utilized in the western United States (US) due to the arid, moisturelimited environment [6,7,[16][17][18][19][20][21][22][23][24][25][26][27][28], until recently, similar studies have been relatively limited in the southeastern US [3,8,14,[29][30][31][32][33][34]. However, Crockett et al [2] established TRCs to be useful and statistically significant proxies even in the humid subtropical climate of northern Florida.…”
Section: Introductionmentioning
confidence: 99%
“…Sites were selected for this study based on previous research for their hydroclimate sensitivity (Stahle and Cleaveland 1994, Stahle et al 2006, Harley et al 2017, Therrell et al 2020, Vines et al 2021. Thirty trees at each site were each cored twice using a 5 mm Haglof increment borer above buttress height.…”
Section: Tree-ring Datamentioning
confidence: 99%
“…If high river flows caused by anomalously high precipitation occur in the later growing season (June-October), earlywood production may begin again thus producing a false ring, similar to how North American monsoon rains in the southwestern US trigger renewed growth in Pinus ponderosa (Morino et al 2021). Therrell et al (2020) suggest that years with a stand-wide high production of false rings frequently occur as a result of tropical cyclone rainfall, and Mitchell et al (2019) demonstrated that Pinus palustris false rings occurred as a result of tropical cyclone occurrences from June-October as most Atlantic hurricane rainfall along the Gulf of Mexico coast occurs during June-September Tucker 2018, Bregy et al 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation